Isolation And Characterization Of Possible New Bacteriophage From Goat Faeces - Sellvam, Dharmela (2012)
Bacteriophages or phages are group of viruses that would infect and lyse bacteria. Phages entities are one of the most abundant life form on earth with the total estimation number of 1031 phages. Until today, only ~6,000 types of phages have been discovered and majority of them are dsDNA tailed phages. The use of phages as a treatment for bacterial infections has regained the attention due to the emergence of antibiotic multi-resistant bacterial strains. In addition, the diverse and enormous phages also contribute to the bacteriophage therapy. A potentially new bacteriophage was isolated from goat feces which could add to the number of phages discovered so far and could be used in phage therapy. The isolated phage is a tail phage with similar morphology to other tail phages, yet it has unique tail structure. Other phages have stiff tail structures but this isolated phage has a very flexible tail structure. Besides that, the newly isolated phage has capsid measures 50-57nm in diameter and tail measures 107nm in length with double stranded DNA genome. These characteristics make the isolated phage could be grouped into the family of Siphoviridae. The isolated phage shows quite different physiochemical characteristics as compared to a common tailed phage. The isolated phage has wide range of temperature and pH tolerance for its survival compared to other tail phage such as T4, with temperature of 700C and pH 5-11. Proteomic and genomic analysis show differences between the isolated phage when compared to common phage. Genome size estimation of the isolated phage is around 30kbp – 40kbp. Based on the morphology, physiochemical, proteomic and genomic analysis results, the isolated phage could be a new addition to the list of viruses in International Committee on Taxonomy of Viruses (ICTV) database.